Evaluation of Bioactive Compounds and Chemical Elements in Herbs: Effectiveness of Choline Chloride-Based Deep Eutectic Solvents in Ultrasound-Assisted Extraction - Aleksandra Szydłowska-Czerniak; Agnieszka Kowaluk; Michał Strzelec; Tomasz Sawicki; Małgorzata Tańska (Molecules)
In this study, the effectiveness of three choline chloride (ChCl)-based deep eutectic solvents (DESs) formed using malonic acid (MalA), glycerol (Gly), and glucose (Glu) as hydrogen bond donors and two conventional solvents (50% methanol and 50% ethanol) for ultrasonic-assisted extraction (UAE) of antioxidant compounds from four herbs (chamomile, lemon balm, nettle, and spearmint) were estimated. The antioxidant capacity (AC) of the obtained herb extracts was determined by the modified 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), 2,2-diphenyl-1-picrylhydrazyl (DPPH), and cupric reducing antioxidant capacity (CUPRAC) methods. Profiles of phenolic acids, flavonoid aglycones, and flavonoid glycosides in the green and conventional herb extracts were quantitatively analyzed using ultra-performance liquid chromatography (UPLC). Among the prepared DESs, the highest antioxidant potential and total contents of phenolic acids, flavonoid aglycones, and flavonoid glycosides in herb extracts were achieved using ChCl:MalA (1:1). Unexpectedly, the selected green solvents extracted significantly lower amounts of total antioxidants from the investigated herbs than 50% alcohols. Additionally, macroelements (K, Na, Ca, Mg), micronutrients (Mn, Zn, Fe, Cu), and a toxic element (Cd) in four herbs were analyzed using inductively coupled plasma–mass spectrometry (ICP–MS). Determining the compositions of antioxidants and elements in herbs is essential for understanding their nutritive importance when applied in the food, cosmetic, and pharmaceutical industries.